1992
DOI: 10.1254/jjp.59.435
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Naloxone and Levallorphan on the Spinal Cord Reflex Potentials under the Spinal Ischemic Condition in Cats

Abstract: ABSTRACT-The spinal reflex potentials elicited by electrical stimulation of the tibial nerve were re corded from the lumbo-sacral ventral root in spinal cats. When the thoracic aorta and the bilateral in ternal mammary arteries were occluded for 10 min, the potentials were completely depressed. Reap pearance of these potentials could be observed at about 10 min after removal of the occlusion and they gradually recovered. Intravenous injection of naloxone (1 or 10 mg/kg) or levallorphan (0.1 mg/kg) together wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1993
1993
1995
1995

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…An occlusion of 10 min was repeated at an interval of more than 110 min. We have previously reported that the recovery process of the reflex potentials was reproducible when the occlusion was repeated two or three times under this experimental condition (11). In other words, there were no significant differences in the recovery of the amplitude of MSR potentials and the area of PSR potentials among the first, second and third occlusion.…”
Section: Experimental Protocol and Drugssupporting
confidence: 49%
See 2 more Smart Citations
“…An occlusion of 10 min was repeated at an interval of more than 110 min. We have previously reported that the recovery process of the reflex potentials was reproducible when the occlusion was repeated two or three times under this experimental condition (11). In other words, there were no significant differences in the recovery of the amplitude of MSR potentials and the area of PSR potentials among the first, second and third occlusion.…”
Section: Experimental Protocol and Drugssupporting
confidence: 49%
“…Since levallorphan is a K-opiate receptor agonist and a p-opiate receptor antagonist, they concluded that c-opiate receptor stimulation may be beneficial for protection against ischemic neural tissues. In our previous study (11), morphine failed to affect the recovery of PSR potentials after a brief spinal cord ischemia, although naloxone and levallorphan promoted the recovery. Therefore, it is unlikely that naloxone improved the functional recovery by antagonizing opiate receptor, although we can not completely exclude this possibility from the present study.…”
Section: Effects Of Gabaergic Drugs On the Recovery Of Spinal Reflex mentioning
confidence: 68%
See 1 more Smart Citation